If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -3x = 12 + -8x Solving 13 + -3x = 12 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 13 + -3x + 8x = 12 + -8x + 8x Combine like terms: -3x + 8x = 5x 13 + 5x = 12 + -8x + 8x Combine like terms: -8x + 8x = 0 13 + 5x = 12 + 0 13 + 5x = 12 Add '-13' to each side of the equation. 13 + -13 + 5x = 12 + -13 Combine like terms: 13 + -13 = 0 0 + 5x = 12 + -13 5x = 12 + -13 Combine like terms: 12 + -13 = -1 5x = -1 Divide each side by '5'. x = -0.2 Simplifying x = -0.2
| -6h^2-25=0 | | x^2+6x+11=18 | | 2(z-20)+2z=10 | | 5x^2-2=38 | | 1x+30=5x | | 6x+63=9 | | 3p*2-14p-5=0 | | 5x^2+7xy-6y^2= | | -8=z+32 | | 55=c*50 | | 10v^5+32v^4+6v^3= | | 6x^4+5x^3-17x^2-6x=0 | | 17x-y+12x+4y+90=180 | | 10v^4+34v^3+12v^2= | | 5(1x+30)=3x | | 6300-x=4200 | | p(x)=x^2+10x+16 | | e^2x+3=25 | | 10v^5+45v^4+45v^3= | | (4x^2)-6=0 | | 8x-3x+2-x= | | 256=16t^2 | | x^7+x^4+64x+64x^3=0 | | 2x-3=x+(-1) | | 10b-5=5-10b | | y=5-5y | | 15.6+5.2+6.5+d=15.6 | | 4z+b=2x+c | | 4x+48=4x | | 4m^8-25n^6= | | 3x-10y=1 | | -7n-20=-20 |